Psychoeducation against depression, anxiety, alexithymia and fibromyalgia: a pilot study in primary care for patients on sick leave - Eva O. Melin; Ralph Svensson; Hans O. Thulesius (Taylor & Francis Group, 2018)
Objectives: Feasibility testing of a psychoeducational method -The Affect School and Script Analyses (ASSA) - in a Swedish primary care setting. Exploring associations between psychological, and medically unexplained physical symptoms (MUPS). Design: Pilot study. Setting: Three Swedish primary care centers serving 20,000 people. Intervention: 8 weekly 2-hour sessions with a 5-7 participant group led by two instructors - followed by 10 individual hour-long sessions. Subjects: Thirty-six patients, 29 women (81%), on sick-leave due to depression, anxiety, or fibromyalgia. Outcome measures: Feasibility in terms of participation rates and expected improvements of psychological symptoms and MUPS, assessed by self-report instruments pre-, one-week post-, and 18 months post-intervention. Regression coefficients between psychological symptoms and MUPS. Results: The entire 26-hour psychoeducational intervention was completed by 30 patients (83%), and 33 patients (92%) completed the 16-hour Affect School. One-week post-intervention median test score changes were significantly favorable for 27 respondents, with p < .05 after correction for multiple testing for 9 of 11 measures (depression, anxiety, alexithymia, MUPS, general health, self-affirmation, self-love, self-blame, and self-hate); 18 months post intervention the results remained significantly favorable for 15 respondents for 7 of 11 measures (depression, alexithymia, MUPS, general health, self-affirmation, self-love, and self-hate). Conclusions: A psychoeducational method previously untested in primary care for mostly women patients on sick-leave due to depression, anxiety, or fibromyalgia had >80% participation rates, and clear improvements of self-assessed psychological symptoms and MUPS. The ASSA intervention thus showed adequate feasibility in a Swedish primary care setting.Key Points  A pilot study of a psychoeducational intervention - The Affect School and Script Analyses (ASSA) - was performed in primary care   • The intervention showed feasibility for patients on sick-leave due to depression, anxiety, or fibromyalgia   • 92% completed the 8 weeks/16 hours Affect School and 83% completed the entire 26-hour ASSA intervention   • 9 of 11 self-reported measures improved significantly one-week post intervention   • 7 of 11 self-reported measures improved significantly 18 months post-intervention